Baseline profiles of auditory, vestibular, and visual functions in youth tackle football players - White-Schwoch, Travis (Concussion, 2020)
AIM: Neurosensory tests have emerged as components of sport-related concussion management. Limited normative data are available in healthy, nonconcussed youth athletes. PATIENTS & METHODS/RESULTS: In 2017 and 2018, we tested 108 youth tackle football players immediately before their seasons on the frequency-following response, Balance Error Scoring System, and King-Devick test. We compared results with published data in older and/or and nonathlete populations. Performance on all tests improved with age. Frequency-following response and Balance Error Scoring System results aligned with socioeconomic status. Performance was not correlated across neurosensory domains. CONCLUSION: Baseline neurosensory functions in seven 14-year-old male tackle football players are consistent with previously published data. Results reinforce the need for individual baselines or demographic-specific norms and the use of multiple neurosensory measures in sport-related concussion management.